Effectiveness and safety of apixaban versus warfarin in non-valvular atrial fibrillation patients in “real-world” clinical practice - Li, Xiaoyan; Deitelzweig, Steve; Keshishian, Allison; Hamilton, Melissa; Horblyuk, Ruslan; Gupta, Kiran; Luo, Xuemei; Mardekian, Jack; Friend, Keith; Nadkarni, Anagha; Pan, Xianying; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2017)
The ARISTOTLE trial showed a risk reduction of stroke/systemic embolism (SE) and major bleeding in non-valvular atrial fibrillation (NVAF) patients treated with apixaban compared to warfarin. This retrospective study used four large US claims databases (MarketScan, PharMetrics, Optum, and Humana) of NVAF patients newly initiating apixaban or warfarin from January 1, 2013 to September 30, 2015. After 1:1 warfarin-apixaban propensity score matching (PSM) within each database, the resulting patient records were pooled. Kaplan-Meier curves and Cox proportional hazards models were used to estimate the cumulative incidence and hazard ratios (HRs) of stroke/SE and major bleeding (identified using the first listed diagnosis of inpatient claims) within one year of therapy initiation. The study included a total of 76,940 (38,470 warfarin and 38,470 apixaban) patients. Among the 38,470 matched pairs, 14,563 were from MarketScan, 7,683 were from PharMetrics, 7,894 were from Optum, and 8,330 were from Humana. Baseline characteristics were balanced between the two cohorts with a mean (standard deviation [SD]) age of 71 (12) years and a mean (SD) CHA2DS2-VASc score of 3.2 (1.7). Apixaban initiators had a significantly lower risk of stroke/SE (HR: 0.67, 95 % CI: 0.59–0.76) and major bleeding (HR: 0.60, 95 % CI: 0.54–0.65) than warfarin initiators. Different types of stroke/SE and major bleeding – including ischaemic stroke, haemorrhagic stroke, SE, intracranial haemorrhage, gastrointestinal bleeding, and other major bleeding – were all significantly lower for apixaban compared to warfarin treatment. Subgroup analyses (apixaban dosage, age strata, CHA2DS2-VASc or HAS-BLED score strata, or dataset source) all show consistently lower risks of stroke/SE and major bleeding associated with apixaban as compared to warfarin treatment. This is the largest “real-world” study on apixaban effectiveness and safety to date, showing that apixaban initiation was associated with significant risk reductions in stroke/SE and major bleeding compared to warfarin initiation after PSM. These benefits were consistent across various high-risk subgroups and both the standard-and low-dose apixaban dose regimens.Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Apixaban; warfarin; non-valvular atrial fibrillation; stroke; major bleeding